1996
DOI: 10.1111/j.1365-2958.1996.tb02515.x
|View full text |Cite
|
Sign up to set email alerts
|

RAG3 gene and transcriptional regulation of the pyruvate decarboxylase gene in Kluyveromyces lactis

Abstract: The RAG3 gene has been cloned from a Kluyveromyces lactis genomic library by complementation of the rag3 mutation, which shows impaired fermentative growth on glucose in the presence of respiratory inhibitors. From the nucleotide sequence of the cloned DNA, which contained an open reading frame of 765 codons, the predicted protein is 49.5% identical to the Pdc2 protein of Saccharomyces cerevisiae, a regulator of pyruvate decarboxylase in this yeast. Measurement of the pyruvate decarboxylase activity in the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Ottaviano et al (52), using a K. lactis strain with KlPDC1 deleted and harboring a KlPDC1-lacZ fusion gene, searched for mutants that abolished ␤-galactosidase production. One such mutant turned out to harbor a mutation in RAG3, a gene encoding a protein with important sequence similarity to the Pdc2 protein of S. cerevisiae (55). A two-hybrid assay showed interaction between Rag3 and KlPdc1, an interaction confirmed by coimmunoprecipitation experiments.…”
Section: Pyruvate Decarboxylase Regulates the Transcription Of Its Enmentioning
confidence: 93%
“…Ottaviano et al (52), using a K. lactis strain with KlPDC1 deleted and harboring a KlPDC1-lacZ fusion gene, searched for mutants that abolished ␤-galactosidase production. One such mutant turned out to harbor a mutation in RAG3, a gene encoding a protein with important sequence similarity to the Pdc2 protein of S. cerevisiae (55). A two-hybrid assay showed interaction between Rag3 and KlPdc1, an interaction confirmed by coimmunoprecipitation experiments.…”
Section: Pyruvate Decarboxylase Regulates the Transcription Of Its Enmentioning
confidence: 93%
“…The well-documented influence of several positive effectors upon KlPDC1 expression (glucose metabolism [2,17,24], hypoxia [5], and the presence of several putative consensus sequences for transcription factors [5]) suggests that the promoter activity could be the result of different stimuli which might not necessarily be synergic. In order to get rid of interfering regulations and to identify a promoter sequence specifically responding to hypoxia, we decided to assay a panel of promoter sequences, generated by enzymatic digestions and/or PCR amplification of the KlPDC1 promoter sequence, as hypoxic mediators of lacZ gene expression.…”
Section: Production Of Recombinant C-33 Protein From Hepatitis C Virumentioning
confidence: 99%
“…In contrast, in the Crabtree-negative yeast Kluyveromyces lactis both respiratory and fermentative pathways co-exist during growth on glucose (De Deken, 1966;Breunig et al, 2000), although respiration appears to be dispensable since antimycin A (AA) does not inhibit growth on glucose (Rag + phenotype) (Goffrini et al, 1989; Wésolowski-Louvel et al, 1992a). Sensitivity to AA on glucose (Rag -) is associated with mutations in genes encoding glycolytic enzymes, glucose transporters and sensing components, as well as their regulatory factors (Goffrini et al, 1991; Wésolowski-Louvel et al, 1992b;Prior et al, 1993; Bianchi et al, 1996;Prior et al, 1996;Blaisonneau et al, 1997;Betina et al, 2001; Lemaire & Wésolowski-Louvel, 2004; Hnatova et al, 2008).During the characterization of the putative cell cycle gene KlHSL1 in K. lactis, we found that its deletion led to a Rag -phenotype, suggesting involvement in glucose metabolism. To identify the relationship between RAG and KlHSL1, rag and Klhsl1D mutant strains were further analysed.…”
mentioning
confidence: 99%